IMMU-01. IMMUNE CHECKPOINT INHIBITION FOR PEDIATRIC CNS TUMORS: A SINGLE INSTITUTION EXPERIENCE. (4th December 2020) - Cacciotti, Chantel; Choi, Jungwhan; Zimmerman, Mary Ann; Tierney, Elise; Chordas, Christine; Clymer, Jessica; Chi, Susan; Yeo, Kee Kiat
Abstract: INTRODUCTION: Immune checkpoint inhibition through PD-1 and CTLA-4 blockade has shown efficacy in some adult malignancies and is being investigated in pediatrics. We describe our institutional experience with immune checkpoint inhibition in pediatric CNS tumors. METHODS: We performed a retrospective chart review of patients with recurrent, progressive, or refractory pediatric CNS tumors treated with immunotherapy at Dana-Farber/Boston Children's Hospital between 2018–2019. RESULTS: Eleven patients were identified, with median age of 11 years (range:3–9). Diagnoses included DIPG (n=3), HGG (n=4), ependymoma (n=1), craniopharyngioma (n=1), HGNET (n=1) and NGGCT (n=1). Eight patients had recurrent disease (5 local; 3 disseminated); three had refractory disease (non-recurrent). Nine patients were treated with combination therapy (ipilimumab/nivolumab); two patients received monotherapy with either nivolumab or pembrolizumab. Median time from initial diagnosis-to-treatment was 8 months (range 0.8–156). Ten patients received radiation therapy (RT) prior to immunotherapy, with one receiving concurrent RT. Median duration of treatment was 6.1 months (range:1–19). Therapy was discontinued in nine patients: seven due to disease progression and two due to adverse events (colitis, transaminitis). Other pertinent toxicities included type 1 diabetes, hypothyroidism and skin toxicity. Based on iRANO criteria, best responses included partial (n=4), stable (n=6) and progressive disease (n=1). Durable response (>12months) was noted in two patients (HGG and progressive NGGCT). CONCLUSION: Immune checkpoint inhibition appears to have clinical benefit and is relatively well tolerated in this cohort of patients. Results from recently completed prospective clinical trials will be critical to inform clinical decisions.